Educator Beliefs Around Supporting Early Self-Regulation: Development and Evaluation of the Self-Regulation Knowledge, Attitudes and Self-Efficacy Scale - Vasseleu, Elena; Neilsen-Hewett, Cathrine; Ehrich, John; Cliff, Ken; Howard, Steven James (Frontiers in Education, 2021)
The current study sought to investigate the extent to which early childhood educators’ confidence in knowledge, attitudes and self-efficacy for supporting early self-regulation predicted educator behavior and children’s self-regulation outcomes. Data from a diverse sample of 165 early childhood educators participating in a cluster Randomized Control Trial evaluation of a self-regulation intervention were utilized to evaluate the construct validity, reliability and predictive properties of the Self-Regulation Knowledge, Attitudes and Self-Efficacy scale. Evaluation via traditional (EFA, Cronbach’s Alpha) and modern approaches (Rasch Analysis) yielded a valid and reliable 25-item scale, comprising three distinct yet related subscales (i.e. confidence in knowledge, attitudes, self-efficacy). For educators assigned to the intervention group, self-efficacy significantly predicted educators perceived competency to implement the self-regulation intervention as well as their perceptions around the effectiveness of the intervention to enhance children’s self-regulation. For educators assigned to the control group (i.e. practice as usual), educator attitudes longitudinally predicted children’s end-of-year status and change in self-regulation (over 6 months later). Findings from this study suggest the importance of pre-school educators’ beliefs for fostering early self-regulation and highlight a need to further explore the impact of these beliefs with regard to educator engagement with intervention.